Preparation and properties of a novel quaternary copolymerized thermoplastic polyimide - X. Liu; X. W. Cao; G. J. He; T. C. Xing (eXPRESS Polymer Letters)
A series of quaternary copolymerized thermoplastic polyimides (PI) films with good thermal resistance has been synthesized via two-step method from bicomponent isomeric dianhydrides, 2,3′,3,4′-biphenyltetracarboxylic dianhydride (α-BPDA) and 3,3′,4,4′-biphenyltetracarboxylic dianhydride (s-BPDA), and bicomponent flexible diamines, 4,4′-oxydianiline (ODA) and 1,3-bis(4′-aminophenoxy)benzene (TPE-R). By adjusting the molar ratio of dianhydrides to diamines, its effects on the thermal stability, thermoplasticity and solubility of PI films were investigated in detail. The results showed that these quaternary copolymerized PI films were in possession of both thermoplasticity and excellent thermal stability. It is derived from the synergetic effect of isomeric dianhydrides and flexible diamines. It has also been found that there is one critical molar ratio between dianhydrides and diamines, that is, α-BPDA:s-BPDA:ODA:TPE-R = 50:50:50:50, at which the overall performance is optimal.